An evaluation of persistence of postdischarge symptoms in survivors of COVID-19 infection - Ilankumaran Mookkiah; Mandeep Kaur; Arun Kumar Yadav; Saurabh Bobdey; Prabhakar Teli; Dharamjeet Singh Faujdar; S Vijay Bhaskar; Saibal Adhya; S K Kaushik (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2022)
Background: The COVID-19 pandemic has affected almost 100 million people worldwide. Although the disease spectrum has still not been fully understood, there have been the reports of the persistence of symptoms well beyond the acute stage or after discharge from the hospital. Therefore, there is a need to document the persistence of symptoms to identify and provide physical as well as psychosocial support for ensuring the complete recovery of COVID-19 survivors. The present study examines the postacute stage persistence of symptoms in severe acute respiratory syndrome-coronavirus-2 patients. Materials and Methods: A longitudinal follow-up study was conducted on 1170 patients discharged from COVID hospital. All the study participants were contacted after discharge and at 7-day intervals for 42 days, and details of the persistence of symptoms were sought from them. Results: It was found that 43.8% of patients had persistence of symptoms, and 12.4% had symptoms even after 30 days of discharge from the hospital. Among symptoms, the most common persisting symptom was found to be fatigue (26%) followed by respiratory difficulty. The presence of comorbidity (odds ratio 1.61, 95% confidence interval 1.56–2.25, P < 0.01) and moderate/severe disease were found to be independent risk factors for the persistence of COVID-related symptoms. Conclusion: The findings of the study indicate that a large number of COVID-19 survivors continue to suffer from COVID-19 symptoms well after the recovery from the acute stage (discharge from hospital). Therefore, there is a genuine need for instituting measures for the monitoring of patients postdischarge and if required providing treatment to those having persistent symptoms of COVID-19.